Heptagon-Containing Saddle-Shaped Nanographenes: Self-Association and Complexation Studies with Polycyclic Aromatic Hydrocarbons and Fullerenes - David, Arthur H. G.; Míguez-Lago, Sandra; Cruz, Carlos M.; Cuerva, Juan M.; Blanco, Victor; Campaña, Araceli G. (Organic Materials, 2021)
Supramolecular interactions between molecules of the same or different nature determine to a great extent the degree of their applicability in many fields of science. To this regard, planar polycyclic aromatic hydrocarbons (PAHs) and their nanometric congeners, nanographenes (NGs), as well as positively curved ones, as for instance corannulene, have been extensively explored. However, negatively curved saddle-shaped NGs have remained a curiosity to date within this field. Therefore, here we communicate the first systematic study on the supramolecular behavior of heptagon-containing hexa-peri-hexabenzocoronene analogues. Thus, their self-association and host–guest complexation processes with both flat and curved PAHs, and fullerenes have been studied by means of 1H and 13C NMR titrations in solution, identifying C70 as one of the guests with the highest association constant among all the ones tested.
Keywords: nanographenes; contorted aromatics; supramolecular chemistry; host–guest systems; heptacyclic polyarenes; molecular recognition